2022
DOI: 10.3389/fmicb.2022.828984
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hypericin as a Candidate Repurposed Therapeutic Agent for COVID-19 and Its Potential Anti-SARS-CoV-2 Activity

Abstract: The COVID-19 pandemic has had an unprecedented impact on the global economy and public health. Its etiologic agent, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is highly transmissible, pathogenic and has a rapid global spread. Currently, the increase in the number of new confirmed cases has been slowed down due to the increase of vaccination in some regions of the world. Still, the rise of new variants has influenced the detection of additional waves of rising cases that some countries hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
0
15
0
1
Order By: Relevance
“…Furthermore, pre-treatments of cells do not block virus infectivity, arguing against a Hypericum perforatum -mediated blockade of the SARS-CoV-2 receptor ACE2. On the other hand, potential modes of antiviral actions of Hypericum perforatum against SARS-CoV-2 were introduced, since hypericin and pseudohypericin were anticipated, by molecular docking, to form a stable complex with the main (3CL) protease or the RNA polymerase of the SARS-CoV-2 [ 62 , 63 ] or had a high affinity toward SARS-CoV-2 basic proteins [ 64 ] but with only little clarification about biological evidence so far. However, it was found that some plant polyphenols could inhibit the 3CL protease using certain experimental settings [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pre-treatments of cells do not block virus infectivity, arguing against a Hypericum perforatum -mediated blockade of the SARS-CoV-2 receptor ACE2. On the other hand, potential modes of antiviral actions of Hypericum perforatum against SARS-CoV-2 were introduced, since hypericin and pseudohypericin were anticipated, by molecular docking, to form a stable complex with the main (3CL) protease or the RNA polymerase of the SARS-CoV-2 [ 62 , 63 ] or had a high affinity toward SARS-CoV-2 basic proteins [ 64 ] but with only little clarification about biological evidence so far. However, it was found that some plant polyphenols could inhibit the 3CL protease using certain experimental settings [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, agathisflavone demonstrates a high binding affinity to the helicase (7NIO), main protease (7AR5), and NSP15 (6VWW), and hypericin demonstrates strong binding to the main protease (6Y2E), NSP9 (6WXD), and the spike protein (6VXX). Other molecular docking studies have shown that our main protease leads agathisflavone, 94 amentoflavone, 95 ginkgetin, 96 procyanidin b2, 97 bilobetin, 96 and hypericin 98 are good binders against the main protease. Moreover, we found that other molecular docking studies mention some of the same interacting residues that we observed for our main protease leads hypericin, 99 ginkgetin, 100 bilobetin, 100 and procyanidin b2.…”
Section: Identification Of Lead Phytochemicals and Lead Clustersmentioning
confidence: 85%
“…Moreover, Hypericin obtained promising results with a ΔΔG = -22.704 ± 4.008 Kcal/mol, and thus its antiviral activity was evaluated in Vero E6 cells incubated with the new coronavirus. The results indicated that Hypericin caused a significant reduction of viral RNA in the supernatant at concentrations between 10 and 100 µM and exhibited a low cytotoxic activity at these concentrations [Matos et al 2022].…”
Section: Discussionmentioning
confidence: 99%